1995
DOI: 10.1111/j.1476-5381.1995.tb13225.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitric oxide synthase inhibition, nitric oxide and hydroperoxide on insulin release induced by various secretagogues

Abstract: 1 Recent studies have suggested that the generation of nitric oxide (NO) and hydrogen peroxide (H202) by islet NO synthase and monoamine oxidase, respectively, may have a regulatory influence on insulin secretory processes. We have investigated the pattern of insulin release from isolated islets of Langerhans in the presence of various pharmacological agents known to perturb the intracellular levels of NO and the oxidation state of SH-groups.2 The NO synthase inhibitor, N0-nitro-L-arginine methyl ester (L-NAME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
81
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 30 publications
12
81
1
2
Order By: Relevance
“…The mechanisms of action of NO to restrain glucose-stimulated insulin release are still unclear, although reduction of oxidative metabolism of glucose and thereby reduced ATP generation might play a role in the presence of high concentrations of NO (5,6,23). We have previously hypothesized that S-nitrosylation of the glutathione system and/or important regulatory proteins at distal sites in the secretory process are possible targets (1,16,27,38). In fact, a new proteomic approach in brain tissue has revealed a wide range of metabolic and signaling proteins that might serve as Means Ϯ SE for 6 -8 batches of islets/group, isolated from 6 rats, are shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of action of NO to restrain glucose-stimulated insulin release are still unclear, although reduction of oxidative metabolism of glucose and thereby reduced ATP generation might play a role in the presence of high concentrations of NO (5,6,23). We have previously hypothesized that S-nitrosylation of the glutathione system and/or important regulatory proteins at distal sites in the secretory process are possible targets (1,16,27,38). In fact, a new proteomic approach in brain tissue has revealed a wide range of metabolic and signaling proteins that might serve as Means Ϯ SE for 6 -8 batches of islets/group, isolated from 6 rats, are shown.…”
Section: Discussionmentioning
confidence: 99%
“…Before assay 500 l of H 2O was added, and the samples were sonicated (3 ϫ 5 s) followed by centrifugation (1,100 g) for 15 min. As previously described (27,35), the supernatants were then collected and extracted with water-saturated diethyl ether (4 ϫ 2 ml). The aqueous phase was removed and freeze-dried, using a Lyovac GT 2 freeze dryer.…”
Section: Animalsmentioning
confidence: 99%
“…NOS inhibition has been reported to produce an inhibitory effect (5,(13)(14)(15), a stimulatory effect (6,9,16 -18), and no effect at all (19,20) on insulin release. Similarly, exogenously applied NO has been reported to exert a stimulatory (5,13,14,21,22) and an inhibitory effect (6,18,(23)(24)(25)(26)(27) on insulin release. These discrepant data may be the result of variations in the specifics of the experimental conditions, including differences in the agents used (e.g., NOS substrate, NOS inhibitors, NO donors), the concentration of these agents, whether other stimulatory pathways were activated concurrently (e.g., with glucose), the experimental model used (e.g., ␤-cell line, islets, pancreas), and the species.…”
mentioning
confidence: 97%
“…Some investigations provided evidence that NO, presumably produced by a calcium/calmodulin-dependent constitutive NO synthase (NOS), participates in the signal transduction pathway mediating insulin secretion [6], and that L-arginine-derived NO mediates insulin secretion via stimulation of guanylate cyclase and cGMP formation [7]. Others found no evidence for endogenously produced NO being involved in the initiation of secretagogue-induced insulin release [8] or reported that L-arginine-derived NO may even inhibit insulin release [9].Recently, Willmott et al [10] showed that beta cells preloaded with tryptamine, which accumulates in insulin-containing granules and is co-secreted with insulin, respond to NO by mobilizing Ca 2+ from the endoplasmic reticulum accompanied by a release of tryptamine from the cells. These data corroborate our previous finding that exogenously added NO Diabetologia (1998) Summary Nitric oxide (nitrogen monoxide, NO) acts as a signal transducer in a variety of cells.…”
mentioning
confidence: 99%
“…Some investigations provided evidence that NO, presumably produced by a calcium/calmodulin-dependent constitutive NO synthase (NOS), participates in the signal transduction pathway mediating insulin secretion [6], and that L-arginine-derived NO mediates insulin secretion via stimulation of guanylate cyclase and cGMP formation [7]. Others found no evidence for endogenously produced NO being involved in the initiation of secretagogue-induced insulin release [8] or reported that L-arginine-derived NO may even inhibit insulin release [9].…”
mentioning
confidence: 99%